Innovative Buddhist Women, Swimming against the stream. Edited by Karma Lekshe Tsomo. - Kalab, Milada (Buddhist Studies Review, 2002)
Innovative Buddhist Women, Swimming against the stream. Edited by Karma Lekshe Tsomo. Curzon, Richmond 2000. xviii, 354 pp. Hbk £45.00, pbk £15.99. ISBN (hbk) 0-7007-1219-4, (pbk) 0-7007-1253-4.